De-reification and self-consciousness: The aesthetic mimesis in the thought of Georg Lukács - Potamias, Spyros; Mandilara, Iro (My University, 2023)
In this article, we discuss the de-reifying role of art and its relation with humanity’s self-consciousness, as these are captured in Lukács’ aesthetic thought and, especially, in his work The Specificity of the Aesthetic. Through the discourse on both categories that traverse Lukács oeuvre (totality, reification, imputed consciousness, etc.) and exclusively aesthetic categories (typical, particular, catharsis, mimesis, etc.), we attempt to give prominence to the way in which Lukács conceives artwork’s contribution to the cultivation of humanity’s self-consciousness.
Keywords: aesthetics; art; mimesis; particularity; reification; totality; typical